The application of augmented reality in print media - Margaritopoulos, Merkourios; Georgiadou, Elissavet (Journal of Print and Media Technology Research, 2023)
Augmented reality is a growing research field aiming to enhance the elements of the real world by overlaying additional virtual information. The paper presents augmented reality as an efficient tool of renovating the traditional print media. It includes an introduction to its concept, covering its fundamental principles and technologies, and focuses on its application in print media. It examines the ‘augmented print media’ in terms of the related technologies and reports on distinguished examples of augmented newspapers, magazines, books and packaging products. Finally, the paper attempts to point out the role of augmented reality in redefining the position of print media in the digital world. It studies the differences between print and digital media and proves the contribution of augmented reality in upgrading print media to modern communication media.